The Australian Monstrilloida (Crustacea: Copepoda) II. Cymbasoma Thompson, 1888 - Suárez-Morales, Eduardo; Mckinnon, A. David (Zootaxa, 2016)
Monstrilloid copepods collected during the past two decades from zooplankton surveys in reef and coastal areas of Australia were analyzed. A first contribution included the taxonomic analysis of three genera of the Monstrilloida, Monstrillopsis Sars, 1921, Maemonstrilla Grygier & Ohtsuka, 2008, and the newly described Australomonstrillopsis Suárez-Morales & McKinnon, 2014. In this document a taxonomic analysis of the species belonging to the genus Cymbasoma Thompson, 1888 is provided. A total of 28 species were found, most of them being undescribed. Seventeen species were described based on females only and eight on male specimens while three species were described from both sexes. Males of Australian species of Cymbasoma are distinguished by details of the genital complex, body size and proportions, ornamentation and processes of the cephalic region, number of caudal setae, and the characteristic structure or ornamentation of the genital lappets. Two main groups of males were distinguished on the basis of the number of caudal setae (3 or 4). As for the females, 20 of the 25 new species of Cymbasoma have fifth legs with an unarmed inner lobe and three setae on the outer lobe; one of these species (C. jinigudira sp. nov.) belongs to the C. longispinosum species-group (sensu Üstün et al. 2014). Another group, consisting of five species, has only two setae on the outer (exopodal) lobe. There were no Australian species of Cymbasoma with a single lobe. A species group, named after C. agoense, is proposed to include species sharing a globose body and a female fifth leg with a large endopodal lobe and an outer (exopodal) lobe with two setae. The females of the new species of Cymbasoma from Australia can be distinguished from their known congeners by unique combinations of characters including the type of body ornamentation, body size and shape, antennule armature and proportions, the presence of distinctive features of the legs 1–4, the presence/absence of processes on the genital compound somite, and the presence/absence of a constriction of the anal somite. We report the occurrence of two previously described species, C. agoense Sekiguchi, 1982 from Japan and C. bali Desai & Krishnaswamy, 1962 from India in Australian waters. Considering the addition of the 25 new species here described, the number of nominal species of the genus is now 66. A key to the Australian species of Cymbasoma (males and females) and a map showing their occurrence in Australia are also provided.